1990
DOI: 10.1007/bf00003425
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycogen phosphorylase in the regulation of glycogenolysis by insulin and glucagon in isolated eel (Anguilla rostrata) hepatocytes

Abstract: The effects of porcine, scombroid, and salmon insulins, and bovine and anglerfish glucagons on glycogen depletion and glycogen phosphorylase (GPase) activities were examined in freshly isolated American eel (Anguilla rostrata) hepatocytes. Eel liver GPase in crude homogenates was activated (increase in % GPase a) by phosphorylating conditions and was rapidly inactivated (less than 1 h) when a phosphatase inhibitor (fluoride) was absent. Caffeine inhibits, and AMP activates, the b form of GPase consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Incubation of rainbow trout hepatocytes with glucagon and glucagon-like peptide (GLP) induced an increase in cAMP, GPase-a activity, and glucose release, and a decrease in glycogen level (Puviani et al 1990). In American eel hepatocytes, the magnitude of bovine glucagon effects was dependent on the initial glycogen content of the cells; thus, glucagon increased % GPase-a (represents the ratio of GPase-a to total GPase) only at glycogen concentrations lower than 70 lmol g -1 (Foster and Moon 1990b). A direct relationship between hepatocyte glycogen content and total GSase, total GPase, and GPase-a activities was reported in rainbow trout hepatocytes (Pereira et al 1995).…”
Section: Glycogen Metabolismmentioning
confidence: 84%
See 1 more Smart Citation
“…Incubation of rainbow trout hepatocytes with glucagon and glucagon-like peptide (GLP) induced an increase in cAMP, GPase-a activity, and glucose release, and a decrease in glycogen level (Puviani et al 1990). In American eel hepatocytes, the magnitude of bovine glucagon effects was dependent on the initial glycogen content of the cells; thus, glucagon increased % GPase-a (represents the ratio of GPase-a to total GPase) only at glycogen concentrations lower than 70 lmol g -1 (Foster and Moon 1990b). A direct relationship between hepatocyte glycogen content and total GSase, total GPase, and GPase-a activities was reported in rainbow trout hepatocytes (Pereira et al 1995).…”
Section: Glycogen Metabolismmentioning
confidence: 84%
“…Similarly, in American eel hepatocytes, insulin decreased cAMP levels and total GPase and % GPase-a activities (Foster and Moon 1990b). In contrast, in Atlantic salmon hepatic GPase-a activity increased, whereas GPase b (less active form) activity and glycogen content decreased 30 h after an intraperitoneal injection of insulin (Sundby et al 1991).…”
Section: Glycogen Metabolismmentioning
confidence: 91%
“…Activation of the lipase enzyme by phosphorylation was studied using the 110,000 x g supernatant from livers homogenized in fluoride-containing buffer (buffer E: 10 mM HEPES, 4.5 mM Bmercaptoethanol, 0.18 mM phenylmethylsulphonyl fluoride, 100 mM KF, pH 7.5) (F-inhibits phosphatase; cf., Stalmans and Hers 1975) or in "inhibitor-free" buffer (buffer E without KF) (cf., Foster and Moon 1990). Enzyme-containing supernatant fractions (ca.…”
Section: Enzyme Activationmentioning
confidence: 99%
“…Regarding glucose uptake, in addition to GLUT4 (glucose transporter type 4) translocation to the plasma membrane in response to insulin in fish skeletal muscle (Díaz et al, 2007), both GLUT1 (glucose transporter type 1) and GLUT4 gene expression are regulated by this hormone in vivo and in vitro (Capilla et al, 2002;Díaz et al, 2009). On the other hand, although insulin administration often results in unspecific glycogen fluctuations (Mommsen and Plisetskaya, 1991), the most common response is the depletion of hepatic glycogen stores in vivo (Bhatt et al, 1980;Ottolenghi et al, 1982), while a more consistent glycogenic response is found in vitro (Foster and Moon, 1990;Ottolenghi et al, 1981). The response of muscle glycogen to insulin administration seems to be more consistent, as in several fish species muscle glycogen levels increase following physiological hormone injection (Bhatt et al, 1980;Ottolenghi et al, 1982).…”
Section: Introductionmentioning
confidence: 99%